La dimensión emotiva en la construcción discursiva de la figura de los desaparecidos en Argentina - Battaglino, Vanesa Lorena (EDITORIAL DE LA UNIVERSIDAD NACIONAL DEL SUR, 2021)
In this paper we will reflect on the figure of the disappeared during the last military dictatorship in Argentina (1976-1983), based on the analysis of two opposing discursive logics, one of the military actor and the other of the report Nunca Más (“Never Again”) prepared by the National Commission on the Disappearance of Persons (CONADEP, 1984). The aim is to show the central role played by the emotive dimension in the construction of a biased image of the Other-disappeared, highlighting and canceling certain features of its identity. This will allow us to understand how the emotional repertoire of a society can be manipulated through the use of discourses and estimate its consequences in political life.